Higher IL-1beta level in the follicular liquid of endometriosis compared with non-endometriosis patients - Cahyono Hadi; Djaswadi Dasuki; Ahmad Hamim Sadewa; Indwiani Astuti; Awal Prasetyo (Universitas Airlangga, 2020)
Objective: To ascertain the IL-1b level in the follicular liquid of endometriosis sufferers compared with that of non-endometriosis sufferers. Materials and Methods: The ELISA method, for detecting the IL-1b, is taken from follicular fluid of endometriosis as well as non-endometriosis patients that diagnosed according to the ASRM criteria. Results: The 54 subjects were dominantly endometriosis <34 year old (88.9%).  The IL-1b levels of endometriosis patients and non-endometriosis patients were 82.86 ± 30.15 and 56.05 ± 23.27 respectively (p=0.01). The ROC value of IL-1b was found at a cut-off point of 26 (with the IL-1b cut-off point of 65.16). The discriminating value of AUC (area under curve) was 59.3%. Conclusion: It was concluded that the IL-1b level in endometriosis is higher than that in non- endometriosis.